Joint Forest Management : Perceptions of New Incumbents in Indian Forest Service - Pandey, Gopa (Indian Forester, 1997)
The training pattern of IFS officers recruited by the UPSC is frequently moderated to address the emerging professional needs. Professional training of Indian Forest Service Officers at Indira Gandhi National Forest Academy at Dehra Dun has also been tailored to suit the upcoming socio-economic dimensions of forestry profession in India. A survey of IFS probationers from four batches of Indian Forest Service officer including the first batch which has undergone the latest pattern of on-the-job training sandwiched between Professional and Advance Phases has been conducted to interpret their assumptions and perceptions on the issues of Joint Forest Management in India. Though their exposure to the process is very limited, yet the new generation has expressed some key issues from its objectivity to the problem which needs to be addressed. Most of them have revealed optimistic thoughts about the process and accept JFM as one of the options of regulating forestry in India.